Leptin and Insulin Resistance in Obese Children - Tahir, Noor T.; Ahmed, Hind S.; Gaiz, ALmottesembellah A. (AL-Kindy College Medical Journal, 2014)
Background: Insulin resistance (IR) is the primary metabolic disorder associated with obesity. Obesity is a growing worldwide health problem affecting both adults and children. Objectives: To determine the association between leptin and IR, and to identify the ratio of fasting glucose/leptin (G/L) and insulin/leptin (I/L) as a new simple method for the detection of IR in obese children.Methods: This study was done in the National DiabeticCenter/ AL-Mustansiriya University during the period fromMay 2013 until the end of October 2013. Fasting bloodglucose (FBG), serum insulin, leptin, and lipid profile weremeasured in 52 obese children (24 children with IR and 28without IR); their age range was (5-15) years, they werecompared with 38 healthy children as a control group.Results: Means of FBG, insulin, leptin, total cholesterol(TC), triacylglycerol (TAG), low density lipoproteincholesterol (LDL-C), and non high density lipoproteincholesterol (non HDL-C) were significantly increased inobese children with IR as compared in children without IR,(P